P190 Characteristics and outcome of patients with active tuberculosis requiring intensive care admission, 2010–2015. (15th November 2016) - Shah, NM; Patel, S; Myall, K; Milburn, H; Breen, RA
Abstract : Introduction: Severe tuberculosis (TB) infection requiring admission to the intensive care unit (ICU) has been reported to be associated with a poor prognosis; however, no data on this cohort of patients from the UK is available. We sought to characterise and report the outcome of this patient group, looking to identify prognostic markers of a poor outcome. Methods: All patients admitted to the ICU at our London tertiary referral centre between 01/01/10 and 31/12/15 and coded as having TB were identified and cross-referenced against the London TB register. Results: 29 patients were identified which represents 4% (29/790) of all TB notified at our centre in the study period. Median age was 41 years (22–86); 72% were male. 69% had pulmonary TB; 24% were HIV-infected, with a median CD4 count on admission of 134/uL (17–277). 14% were AFB smear-positive; 79% had culture-positive TB and 86% grew fully-sensitive organisms. The most frequent indications for ICU admission were hypoxic respiratory failure (38%), haemodynamic compromise (24%) and hypercapnic respiratory failure (21%). Median A-a gradient was 12.9 kPa, median PaO2 /FiO2 ratio was 29.9 kPa. 72% required mechanical ventilation (median ventilation days 8.4). Two patients received extracorporeal membrane oxygenation therapy for severe respiratory failure. Median APACHE II score was 16 and median SOFA score was 4. Median length of stay in ICU was 7 days and in hospital was 24. At 30 days, 35% remained in-patients (of which 14% remained in ICU), 59% had been discharged home and 21% had died. Table 1 summarises the differences between survivors and those who died. Conclusion: In our TB population, the requirement for ICU care was infrequent, with respiratory failure being the most common indication. ICU and overall hospital length of stay was prolonged, but with a majority of patients surviving to discharge. Possible markers of a poor outcome include age, and a requirement for cardiovascular/renal support. These markers and TB-related factors now need to be explored in a larger cohort.